Terapi Cuci Hidung dengan Cairan NaCl 0,9 untuk Mengatasi Gangguan Rasa Nyaman terhadap Penderita Rhinitis Alergi - Yanti, Yuli; Fauziah, Chori Ajeng; Rachman, Ivan Arif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe inflammation of the nasal mucosa caused by allergic reactions after exposure to allergens. The method used is a case study approach model. The study results showed that the respondents were adults aged 20 and 22, male and female, and educated as students. The description of the knowledge of both respondents was quite good, after being given counseling, both respondents were good at absorbing the knowledge that had been given. The effectiveness of nasal wash therapy with 0.9% NaCl solution was very effective in both respondents in reducing or eliminating symptoms of allergic rhinitis after application for seven days, thus providing comfort to both respondents. In conclusion, nasal wash therapy with 0.9% NaCl solution is very effective in overcoming discomfort disorders in Allergic Rhinitis sufferers after application for seven days. Keywords: Nasal Wash with 0.9% NaCl Solution, Disturbance of Comfort, Allergic Rhinitis